136 Clinical Outcomes of Testosterone Replacement Therapy in Japanese Patients with Late Onset Hypogonadism (LOH) Syndrome. (1st May 2022) - Kuratsukuri, K; Minami, A; Naganuma, T; Uchida, J
ABSTRACT: Objectives: The Japanese late-onset hypogonadism (LOH) guideline is using serum free testosterone (FT) level for diagnosis of LOH syndrome. On the other hand, the European and American guidelines are using total testosterone level (TT) for diagnosis of LOH syndrome. Serum total testosterone levels below 8 nmol/L (231 ng/dL) require substitution of testosterone in the E.A.U. recommendations. In this study, we compared serum free testosterone level and total testosterone level in patients who visited our LOH syndrome out-patient department. We also investigate clinical outcomes of testosterone replacement therapy (TRT) in patients with LOH syndrome. Material and Methods: Two hundred thirty male patients who visited our LOH syndrome out-patient department from January, 2008 to September, 2017 were targeted at this study. The patient's average age was 55.1 years old. Average of AMS score in patients was 51.7 points. Results: Only 20 patients (8.7%) were low value (less than 2.31ng/ml) and 86 (37.4%) patients were low and borderline value (less than 3.46ng/ml) in serum total testosterone (TT) level. On the other hand, 99 patients (43.1%) were low values (less than 8.5pg/ml), and also 175 examples (76.1%) were low and borderline value (less than 11.8pg/ml) in serum free testosterone (FT) level. Testosterone replacement therapy (TRT) was carried out for 3 months in 84 patients with patient with LOH syndrome. Sixty nine patients (82.1%) were effective for ART. Only four patients dropped out TRT because of dysuria and plethora. Fifty four patients (83%) with patients who were low value (l less than 8.5pg/ml) in serum free testosterone (FT) were effective for ART in 53 patients. Also 25 patients (80.6༅) who was borderline value (less than 11.8pg/ml) in serum free testosterone (FT) level were effective for TRT in 31 patients. Conclusions: Including borderline case, high frequency patient is suited at the diagnostic criteria of LOH syndrome using serum FT value compared to TT value. It might be necessary to also consider measurement of the auxiliary total testosterone, and compensation of the isolation testosterone by age. Testosterone replacement therapy (TRT) was also effective in patients with LOH syndrome not only low value but also borderline value in serum free testosterone (FT). Disclosure: Work supported by industry: no.